ANÁLISE DOS MODELOS DE AVALIAÇÃO PELO LUCRO RESIDUAL E CRESCIMENTO ANORMAL DOS LUCROS: UMA ABORDAGEM PRÁTICA UTILIZANDO PROJEÇÕES DOS ANALISTAS - Almeida, José Elias Feres; Lima, Gerlando Augusto Sampaio Franco de; Lima, Iran Siqueira; Securato, José Roberto (RC&C: Revista de Contabilidade e Controladoria, 2012)
<!–StartFragment–>This paper revisits two valuation models based on accounting figures: the Residual Income Valuation (RIV) and Abnormal Earnings Growth (AEG). Our research design has two approaches: i) we demonstrate theoretical integration of both models; and ii) we show in a practical manner that models converge to the same results based on real data of analysts forecast consensus. We apply statistical tests on empirical data from analyst’s forecasts available on Thomson One Analytics database. We use information of 45 firms listed on the IBovespa segment from BMF&BOVESPA in 2008 with historical data from 2003 to 2007 and analysts’ projections from 2003 to 2010. Our results do not show a significant mean difference of the valuations, but those from the RIV model are more dispersed than those produced by the AEG model. Furthermore, our results are consistent with international evidences and present additional evidences of application of valuation models based on accounting information in Brazil. Our findings support the use of valuation models based on accounting figures by analysts, investors, rating agencies and regulators to provide additional analyses of firm’s future prospects.<!–EndFragment–>